2008
DOI: 10.1021/cm702931b
|View full text |Cite
|
Sign up to set email alerts
|

Organogels Based on Self-Assembly of Diphenylalanine Peptide and Their Application To Immobilize Quantum Dots

Abstract: We report that a single dipeptide (L-Phe-L-Phe, FF), which is probably one of the smallest peptide gelators, can self-assemble into long nanofibrils in organic solvents and entangle further to form gels. The obtained FF gels are responsive to temperature, and the FF sol-gel process is thermoreversible. The formation of such gels may be driven by the hydrogen bond of peptide main chains and the π-π interactions between aromatic residues of the peptide. Lipophilic nanocrystals can be encapsulated into the gel th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
223
2
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(246 citation statements)
references
References 44 publications
(74 reference statements)
15
223
2
5
Order By: Relevance
“…conformation. 65,66 In all cases these structural characteristics are preserved between -50 ºC and +60 ºC, as is demonstrated by the spectra acquired at different temperatures within such interval ( Figure S3). …”
Section: Structure Of the Sheets And Intermolecular Interactionssupporting
confidence: 58%
“…conformation. 65,66 In all cases these structural characteristics are preserved between -50 ºC and +60 ºC, as is demonstrated by the spectra acquired at different temperatures within such interval ( Figure S3). …”
Section: Structure Of the Sheets And Intermolecular Interactionssupporting
confidence: 58%
“…There have been numerous attempts to develop self-assembling peptides since the early 1990s (Ghadiri et al, 1993;Hartgerink et al, 2001;Reches and Gazit, 2003). Among many synthetic peptide building blocks reported to date, diphenylalanine (FF), which constitutes the core recognition motif of Alzheimer's b-amyloid peptide, is one of the simplest peptides, and it self-assembles into many different nanostructures from nanotubes (Reches and Gazit, 2003) to organogels (Yan et al, 2008). Researchers also found that self-assembled diphenylalanine nanostructures possess novel mechanical (Kol et al, 2005;Niu et al, 2007), electrochemical (Yemini et al, 2005), and optical properties ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 , 17 ] Among numerous self-assembling peptides reported to date, diphenylalanine (Phe-Phe, FF) and its derivatives [18][19][20][21][22][23][24][25][26][27][28][29][30] are simplest peptides exhibiting unique mechanical, [ 19 ] electrochemical, [ 20 ] and optical properties [ 21 ] as well as high thermal and chemical stabilities. [ 23 ] It has been reported that they can readily form various nanostructures, including nanotubes, [18][19][20][21][22] nanowires, [23][24][25][26][27] nanospheres, [ 28 ] organogels, [ 29 ] and hydrogels [ 30 ] through a self-assembly process. Here, we fi rst report the synthesis of transition metal phosphate nanotubes for application as a cathode material for rechargeable lithium (Li) ion batteries by using a peptide hydrogel self-assembled from fl uorenylmethoxycarbonyl (Fmoc)-FF [ 30 ] as a template.…”
mentioning
confidence: 99%